2022
DOI: 10.1038/s41598-022-07588-4
|View full text |Cite
|
Sign up to set email alerts
|

Optically-assisted thermophoretic reversible assembly of colloidal particles and E. coli using graphene oxide microstructures

Abstract: Optically-assisted large-scale assembly of nanoparticles have been of recent interest owing to their potential in applications to assemble and manipulate colloidal particles and biological entities. In the recent years, plasmonic heating has been the most popular mechanism to achieve temperature hotspots needed for extended assembly and aggregation. In this work, we present an alternative route to achieving strong thermal gradients that can lead to non-equilibrium transport and assembly of matter. We utilize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…For in vivo applications of optothermal tweezers, Cui et al have demonstrated the use of near-infrared (NIR) laser beams for higher penetration depth and effective biofilm removal, demonstrating the applicability of optothermal tweezers for photothermal therapy (Figure 4c). 52 Moreover, optothermal manipulation has enabled ablation applications, 53 microsurgery, 54 cancer diagnostics, 55 and study of cell−cell communication. 12 Overall, existing optothermal manipulation is well suited for in vitro applications, which can utilize the advantages of a light-absorbing substrate.…”
Section: Applications Of Optothermal Manipulationmentioning
confidence: 99%
“…For in vivo applications of optothermal tweezers, Cui et al have demonstrated the use of near-infrared (NIR) laser beams for higher penetration depth and effective biofilm removal, demonstrating the applicability of optothermal tweezers for photothermal therapy (Figure 4c). 52 Moreover, optothermal manipulation has enabled ablation applications, 53 microsurgery, 54 cancer diagnostics, 55 and study of cell−cell communication. 12 Overall, existing optothermal manipulation is well suited for in vitro applications, which can utilize the advantages of a light-absorbing substrate.…”
Section: Applications Of Optothermal Manipulationmentioning
confidence: 99%
“…The same technique was utilized to demonstrate the rapid and reversible thermophoretic aggregation of silica beads by irradiating thin graphene oxide microplatelet with a 785 nm laser having an intensity value of the order of 50−100 µW µm −2 . [ 161 ] As a biological application, work was extended to study the trapping and photoablation of E. coli bacteria (Figure 13c). The same group used the optothermal conversion capability of the graphene oxide‐coated substrate to generate a microbubble at low intensities of the order of a few µW µm −2 .…”
Section: Optothermal Manipulation Through Non‐plasmonic Heatingmentioning
confidence: 99%
“…Reproduced under the terms of the Creative Commons Attribution 4.0 International CC‐BY License. [ 161 ] Copyright 2022, The Authors, published by Springer Nature. d) Schematic of sample device and motion of microparticles, cell under the temperature gradient generated by heating single‐walled carbon nanotubes, and e) image stack at 0 s and after 30 s, showing particle manipulation by laser‐induced heating of single‐walled carbon nanotube cluster.…”
Section: Optothermal Manipulation Through Non‐plasmonic Heatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although useful, this design of using separate laser beams for trapping and spectroscopy can lead to constraints due to charge state perturbations when an IR excitation is involved 9,13 and may not be conducive in sensitive environments such as a living cell, where exposure to high-power density lasers can potentially lead to denaturing of biomolecules and damage of the cell. This clearly creates an imperative to design and develop nano-optical and optothermophoretic trapping methods [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] in which a single low-power laser can facilitate the capability of trapping and spectroscopic probing and imaging. 29 Recently, we have shown 30 that a drop-casted single gold nanoparticle can drive thermoplasmonic fields, facilitating the trapping of single metallic nanostructures and creating a large assembly at a very low power density (0.01 mW/µm 2 ).…”
mentioning
confidence: 99%